2021
DOI: 10.1002/celc.202001116
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Engineering in a Cathode Composite Based on Garnet‐Type Solid‐State Li‐Ion Battery with High Voltage Cycling

Abstract: Garnet‐type solid electrolyte is a promising candidate for the fabrication of high energy all‐solid‐state Li‐ion batteries (ASSLIBs), but its use is hampered by a large interfacial resistance. Herein, we propose a surface modification and subsequent sintering to enhance the interfacial connection between the cathode and the solid electrolyte. The ASSLIB prepared by this method delivered an initial discharge capacity of ∼66 mAh g−1 (80 °C) at a rate of 0.1 C. However, the poor contact between the cathode and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…However, the loading of the cathode film, which is typically hundreds of nanometers thick, is extremely low. (b) Casting the composite cathode slurry on the top surface of garnet pellets followed by sintering [31][32][33][34][35][36][37][38]. To improve the contact of LCO and garnet, sintering additives such as Li 3 BO 3 (LBO) and its derivatives are added to the composite cathode slurry.…”
Section: Introductionmentioning
confidence: 99%
“…However, the loading of the cathode film, which is typically hundreds of nanometers thick, is extremely low. (b) Casting the composite cathode slurry on the top surface of garnet pellets followed by sintering [31][32][33][34][35][36][37][38]. To improve the contact of LCO and garnet, sintering additives such as Li 3 BO 3 (LBO) and its derivatives are added to the composite cathode slurry.…”
Section: Introductionmentioning
confidence: 99%
“…S1, † and the relative density of the compressed pellets of the pristine LLZTO was 92.44% (Table S2 †), showing an acceptable level compared to other reported results based on the applied pressure of 100 MPa. [42][43][44] After the wet chemical treatment (see the Experimental section), the pristine LLZTO powder was uniformly coated with the Co x B layer. The ICP-OES results indicated that the infused Co x B possessed a close chemical proportion of Co 2.25 B, which was a similar result with the previously reported data.…”
Section: Resultsmentioning
confidence: 99%
“…Oxide ceramics are considered superior to other SEs because of their high Li-ion conductivity and excellent electrochemical stability with cathode materials and with the Li metal anode. 8,9,12 The most commonly used oxide SEs are perovskite where Y= Al or Ga). 6,8,9,12,13,16−21 Most of the oxide SEs are sintered with rare earth and expensive materials at high temperatures (>1000 °C) to reduce the grain boundary resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The high mechanical stability of SEs can suppress Li dendrite formation . Generally, a good SE should have high ionic conductivity and reasonable critical current density to suppress Li dendrite formation across the Li/electrolyte interface, negligible electronic conductivity, a wide electrochemical stability window, and good chemical compatibility with the electrode (cathode and anode) materials. Furthermore, it should have high stability when exposed to air and H 2 O under ambient temperature conditions . Unlike polymer electrolytes, ceramic electrolytes have high Li-ion conductivity, high ionic transfer number, high electrochemical stability, and excellent thermal stability. …”
Section: Introductionmentioning
confidence: 99%